IDENTIFIKASI POTENSI MULTI-BENCANA DI KABUPATEN LANDAK KALIMANTAN BARAT - A Wahyuningtyas; Rahmat Aris Pratomo (Department of Urban and Regional Planning, Diponegoro University, 2015)
One of the important aspects in studies on regional potentials and problems is the sectoral issues in a disaster. It is because disaster is an event or series of events, caused whether by natural or unnatural factors that inflict damages and losses to people and the environment. Landak Regency (Kabupaten) is categorized highly disaster-prone region by the National Disaster Management Agency (BNPB). The aim of this research is to identify the disaster-prone area of Kabupaten Landak. The identification is based on assessment variables of multi-hazards that may occur and threat Kabupaten Landak. The analysis has used geographic information systems, scoring and weighting techniques. Disaster vulnerability was measured based on the existing physical aspects, such as land use, land slope, soil type, and others. It is an explorative and evaluative research with a mix of qualitative and quantitative approaches. The results show that there are disaster potential hazards in Landak Regency, such as flood, landslide, cyclone, bushfire, and forest-fire. Each potential hazard has different vulnerability level and different distribution area based on the risk assessment. © 2015 GJGP UNDIP. All rights reserved